Cover Image. Issue 7 (11th June 2018) - Gjessing, M C; Christensen, D H; Manji, F; Mohammad, S; Petersen, P E; Saure, B; Skjengen, C; Weli, S C; Dale, O B
Abstract : The cover image, by M C Gjessing et al., is based on the Original Article Salmon gill poxvirus disease in Atlantic salmon fry as recognized by improved immunohistochemistry also demonstrates infected cells in non‐respiratory epithelial cells, DOI:10.1111/jfd.12802 .